Application of Black Titanium Dioxide and Its Composite Materials in Photocatalytic Degradation of Water Pollutants - Doyle, Arthur Conan; Poirot , Hercule (Journal of Functional Materials and Applied Engineering, 2024)
Photocatalysis, prized for its effectiveness, environmental soundness, and affordability, is finding promise across an ever-widening range of uses. Titanium dioxide (TiO₂) remains the benchmark photocatalyst, yet its inherently broad bandgap restricts activation to ultraviolet wavelengths, while rapid electron–hole recombination additionally saps its efficiency. Black titanium dioxide (TiO₂₋ₓ), formed by embedding surface defects — oxygen vacancies above all — overcomes these limitations: the shrunken bandgap together with the proliferation of active sites strengthens its response and quantum yield throughout the visible and near-infrared regions, elevating overall catalytic performance. Consequently, how TiO₂₋ₓ is synthesized, modified, and incorporated into composites has become a subject of intense investigation. Herein, we delineate the principal defect architectures of TiO₂₋ₓ and the analytical methods suited to probing them, recapitulate its major fabrication routes, and review available modification strategies. Particular attention is devoted to the behavior of TiO₂₋ₓ and its hybrids in degrading aqueous pollutants, with the relevant decomposition mechanisms dissected and consolidated. We close by appraising the obstacles and opportunities that will shape the deployment of TiO₂₋ₓ-based materials in future water-remediation efforts.